PENGARUH KECERDASAN EMOSIONAL DAN PERILAKU BELAJAR TERHADAP TINGKAT PEMAHAMAN AKUNTANSI DALAM PROSES PEMBELAJARAN DARING (Studi Empiris Pada Mahasiswa Akuntansi Fakultas Ekonomi dan Bisnis Universitas Islam Malang Pada Masa Pembelajaran Daring) - Khoirul Ahmad Afandi; Moh. Amin; Arista Fauzi Kartika Sari (e_Jurnal Ilmiah Riset Akuntansi, 2021)
This study discusses emotional intelligence and learning behavior on the level of accounting understanding in the online learning process. The type of data in this study is quantitative. The sampling method used is using the slovin formula with the data collection method using a questionnaire via google form. The population in this study were students of the Accounting Department, Faculty of Economics and Business, Islamic University of Malang during the online learning period, namely active students from the 2017 - 2019 class as many as 780 students who had taken online lecture courses with predetermined criteria. The results of this study indicate that partially emotional intelligence affects the level of accounting understanding in the online learning process and learning behavior affects the level of accounting understanding in the online learning process. Meanwhile, both variables simultaneously show a significant effect on the level of accounting understanding in the online learning process.Keywords: Emotional Intelligence, Learning Behavior, Accounting Comprehension, Online Learning.